Is the acid-base status at rest related to endurance performance in 10-km runners? - Lourenço, T; Nunes, L; Artioli, G; Martins, L; Brenzikofer, R; Macedo, D. (Journal of Human Sport & Exercise, 2025)
This study aimed to compare acid-base parameters between elite (ER) and amateur (AR) runners at rest and to explore potential correlations with 10-km running. Each participant completed a 10-km time trial on a 400-meter track, underwent an incremental exercise test in laboratory conditions, and provided a resting blood sample for analysis. Capillary blood sample were collected from the fingertip at rest. Measurements included pH, partial pressure of dioxide carbon (pCO2), haematocrit (Hct), haemoglobin (Hb) and lactate (Lac-), sodium (Na+), potassium (K+), chloride (Cl-) and bicarbonate (HCO3-) ions. Base excess (BE) and strong ions difference (SID) was calculated. No significant differences were observed between ER and AR for Hb, K+, Lac-, and pH (p > .05). ER exhibited significantly higher values for HCO3- (ER = 28.5 ± 1.8; AR = 25.7 ± 1.7 mmol L-1), Cl- (ER = 104.4 ± 3.83; AR = 100.1 ± 3.89 mmol L-1), BE (ER = 5.6 ± 1.6; AR = 3.21 ± 1.43 mmol L-1) and pCO2 (ER = 36.9 ± 3.7; AR = 33.9 ± 2.9 mmHg; p < .05). SID (ER = 49.0 ± 5.70; AR = 41.3 ± 5.23 mmol L-1; p < .05) and Na+ (ER = 140.0 ± 4.1; AR = 143.5 ± 3.3mmol L-1; p < .05) were significantly lower in ER. Strong correlations were found between HCO3-, SID, ventilatory threshold parameters and 10-km performance (p < .05). These findings suggest that resting acid-base status can be a useful indicator of 10-km performance and can assist in monitoring training-induced adaptations.